"Pseudophakic Reverse Pupillary Block" Following Yamane Technique Scleral-fixated Intraocular Lens. Issue 7 (July 2020) - Bharathi, Mahesh; Balakrishnan, Divya; Senthil, Sirisha
Abstract : Purpose: The authors report a rare complication of "pseudophakic reverse pupillary block" after a secondary, scleral-fixated intraocular lens implantation using the Yamane technique. Methods/Results: A 52-year-old male patient was referred for uncontrolled intraocular pressure (IOP) despite 3 topical antiglaucoma medications in his right eye (RE). Elevated IOP occurred after the RE cataract surgery performed elsewhere 1 year ago. On examination, the RE visual acuity was 20/60, IOP was 28 mm Hg, the iris showed mid-peripheral transillumination defects with iris chaffing, posterior bowing of the iris with a deep anterior chamber, pigment dispersion, and scleral-fixated intraocular lens (SFIOL). Ultrasound biomicroscopy showed a deep anterior chamber with posterior bowing of iris with concave iris configuration with iridolenticular contact with the SFIOL, suggestive of reverse pupillary block. After laser peripheral iridotomy, the iris moved forward into planar position, iridolenticular contact was relieved with a resolution of the pupillary block, and the IOP reduced to 14 mm Hg. Conclusions: The present case describes a rare complication of "pseudophakic reverse pupillary block" after a glued SFIOL implantation. The probable mechanism for the pupillary block is the reduced gap between the posterior surface of iris and optic of the IOL. This is likely caused by the loss of 5-degree posterior angulation of the 3-piece IOL because of stretching of the haptics leading to an increase in the iridolenticular contact and reverse pupillary block and elevated IOP. The persistent anterior chamber inflammation as a result of iris chaffing and pigment dispersion could also contribute to compromised trabecular outflow and further IOP elevation. Reverse pupillary block can occur after a glued SFIOL implantation that can be relieved by a laser peripheral iridotomy. The authors recommend either preoperative laser peripheral iridotomy or surgical iridectomy intraoperatively in eyes with a glued intraocular lens to prevent this rare complication.